Heat Shock Protein-70 Levels Are Associated With a State of Oxidative Damage in the Development of Bronchopulmonary Dysplasia - Hsiao, Chien-Chou; Lee, Cheng-Han; Yang, Rei-Cheng; Chen, Jia-Yuh; Su, Tzu-Cheng; Chang, Yu-Jun; Lin, Ching-Yuang; Tsai, Yi-Giien (Frontiers in Pediatrics, 2021)
Background: Heat shock protein-70 (Hsp-70) exhibits cytoprotective effects against oxidative stress-induced airway injury. This study aimed to examine Hsp-70 and 8-hydroxy-2′-deoxyguanosine (8-OHdG) from tracheal aspirates (TA) in very low-birth weight (VLBW) preterm infants to predict the development of bronchopulmonary dysplasia (BPD). Methods: This birth cohort study enrolled 109 VLBW preterm infants, including 32 infants who developed BPD. Hsp-70 and 8-OHdG concentrations from TA were measured by immunoassay. The apoptosis of TA epithelial cells obtained on Day 28 after birth was measured using annexin-V staining assay. Results: Hsp-70 and 8-OHdG levels in TA fluid were persistently increased from Day 1 to Day 28 of life in the BPD group. Multiple linear regression analysis demonstrated that BPD was significantly associated with gestational age, respiratory distress syndrome, and TA Hsp-70 and 8-OHdG levels on post-natal Day 28. The TA Hsp-70 level positively correlated with TA 8-OHdG level on the Day 1 (r = 0.47) and Day 28 of life (r = 0.68). Incubation of recombinant Hsp-70 with primary epithelial cells derived from TA of patients decreased hydrogen peroxide-induced epithelial cell death. Conclusions: Hsp-70 levels are associated with a state of oxidative injury in the development of BPD.